Integrasi Pendidikan Karakter dalam Pembelajaran sebagai Upaya Pencegahan terhadap Maraknya Isu Plagiarisme dalam Dunia Pendidikan - Paul Usmany; Irmawati Irmawati; Ivon Mukaddamah; Anggitya Alfiansari; Budi Mardikawati; Hadirman Hadirman (Departement of Mathematics Education, 2024)
The issue of plagiarism has become a major concern in the world of education, considering its negative impact on academic integrity and student learning. In this research, we investigate the potential of integrating character education in learning as a prevention strategy against the prevalence of plagiarism among students. The research method used involved observing two groups of students: one group received learning with an integrated approach to character education, while the other group did not. The research results showed that students who were involved in learning with integrated character education showed an increased understanding of academic integrity and the risk of plagiarism. In addition, they also showed more positive attitudes towards academic integrity and were more careful in reporting reference sources in their assignments. These findings indicate that the plagiarism prevention approach needs to involve building strong character and awareness of ethical values. In conclusion, integrating character education in learning is an important step in reducing incidents of plagiarism among students. Continuous efforts are needed from all stakeholders to implement and support the implementation of character education in educational contexts to ensure the sustainability of the positive effects achieved through this approach.